Differentiation therapy targeting the stalled epigenetic developmental programs in pediatric high-grade gliomas - Wang Xiang; Xiaolin Zhang; Minhai Dong; Lijun Wan; Bin Zhang; Feng Wan (Pharmacological Research)
Pediatric high-grade gliomas (pHGGs) are the most common brain malignancies in children and are characterized by blocked differentiation. The epigenetic landscape of pHGGs, particularly the H3K27-altered and H3G34-mutant subtypes, suggests these tumors may be particularly susceptible to strategies that target blocked differentiation. Differentiation therapy aims to overcome this differentiation blockade by promoting glioma cell differentiation into more mature and less malignant cells. Epigenetic modulators, including inhibitors of histone deacetylase (HDAC), enhancer of zeste homolog 2 (EZH2), BRG1/BRM-associated factor (BAF) complex, have shown promise in preclinical studies of pHGGs by altering the differentiation program of glioma cells. Although challenges remain in overcoming tumor cell heterogeneity, induced differentiation therapy holds promise for treating these currently incurable pediatric brain cancers.